A ratiometric fluorescent probe based on sulfur quantum dots and calcium ion for sensitive and visual detection of doxycycline in food. (15th September 2021) - Zhuang, Yuerui; Lin, Bixia; Yu, Ying; Wang, Yumin; Zhang, Li; Cao, Yujuan; Guo, Manli
Highlights: Ratiometric fluorescent probe based on S dots/Ca 2+ is used to detect doxycycline. The ratiometric fluorescence method exhibits good accuracy and high sensitivity. Change in fluorescence color is used for visual semi-quantitative detection of doxycycline. Abstract: The residue of doxycycline in food can cause harm to human. Therefore, the detection of doxycycline residue is necessary. Herein, a ratiometric fluorescent probe was designed based on sulfur quantum dots (S dots) and Ca 2+ . Due to static quenching and inter filter effect between doxycycline and S dots, doxycycline quenched fluorescence of S dots at 450 nm. Meanwhile, doxycycline and Ca 2+ formed fluorescent complex through coordination to produce new peak at 520 nm. The ratio of fluorescence intensity (F520 /F450 ) and doxycycline concentration showed good linear relationship with detection limit of 0.19 μM. The fluorescence color of S dots/Ca 2+ changed from blue to light green with increasing doxycycline concentration, which was applied for visual semi-quantitative detection of doxycycline. Moreover, the method was used for detecting doxycycline in milk and fish samples with recoveries in the range of 91%-110%. The method showed good application potential in detection of doxycycline in food samples.